(untitled) - Roberts, R. A. J. (Rome, 2005)
This publication is primarily concerned with risks to arable and horticultural crops, and the applicability of insurance to managing these risks. Its purpose is to provide an introductory overview of crop and forestry insurance. It begins by defining the boundaries for these types of insurance products in order to assist those interested in exploring and exploiting this financial mechanism. It then outlines how to proceed with planning for crop insurance within the established boundaries. While recognizing that classic, damage-based and yield-based insurance products account for the bulk of all crop insurance written globally, the booklet also points out the dynamism of research and development into new insurance mechanisms.
Keywords: Crop insurance,Bảo hiểm cây trồng; Developing countries,Phát triển đất nước